TRANSMISSION PROBLEMS THE LEASING COMPANY OF THE RUSSIAN FEDERATION OF EQUIPMENT FOR USE IN ACCORDANCE WITH THE ISLAMIC BANKING - A. A. Al-Azzawi (Вестник университета, 2017)
This article discusses of the problem transferring of the leasing company of the Russian Federation of equipment for use in accordance with the Islamic banking, the study of traditional financial leasing in comparison with the Islamic leasing (Ijarah) and its variations, the fundamental difference between the traditional contract, Ijara leasing contract, the prerequisites for promotion on the Russian market of Islamic leasing.